PERAN GANDA PEREMPUAN DAN KESETARAAN GENDER - Dwi Edi Wibowo (UIN K.H. Abdurrahman Wahid Pekalongan, 2011)
Abstract : Woman partisipation consists of tradidition and trasition roles.The tradition or domestic role includes women as a wife, mother and household manager. Meanwhile the transition or public role covers woman as a labor , member of society and development as a whole. Nowadays, the phenomenon in the society is woman tends to work harder to eran money for the family and to express themselves. One indicator of woman role in national deveploment can be seen from an increase in variety of woman job, it does not mean that the woman welfare increase automatically. The woman face dicrimation, not pnly in domestic sector but also in public sector. Therefore, the dynamic charateristic of woman multifunction is important to be learned